2020
DOI: 10.1364/oe.384630
|View full text |Cite
|
Sign up to set email alerts
|

Broadly tunable linewidth-invariant Raman Stokes comb for selective resonance photoionization

Abstract: We demonstrate a continuously tunable, multi-Stokes Raman laser operating in the visible range (420 - 600 nm). Full spectral coverage was achieved by efficiently cascading the Raman shifted output of a tunable, frequency-doubled Ti:Sapphire laser. Using an optimized hemi-spherical external Raman cavity composed only of a diamond crystal and a single reflecting mirror, producing high power output at high conversion efficiency (>60 % from pump to Stokes) for a broad range of wavelengths across the visible. En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The resulting Stokes pulses have non-Gaussian envelopes and a duration that is considerably shorter than the pump pulse. Such effect was experimentally observed also in [9].…”
Section: Widely Tunable Diamond Raman Laser Designsupporting
confidence: 64%
See 2 more Smart Citations
“…The resulting Stokes pulses have non-Gaussian envelopes and a duration that is considerably shorter than the pump pulse. Such effect was experimentally observed also in [9].…”
Section: Widely Tunable Diamond Raman Laser Designsupporting
confidence: 64%
“…This laser source was characterized and tested for resonant ionization spectroscopy experiments, by exciting the atomic transition 4s 2 1 S 0 → 4s4p 1 P 0 1 of calcium at 422.79 nm. The Ca + isotopes were produced inside an atomic beam unit in cross-beam geometry, where a time-of-flight spectrometer was used to measure the ion signal [9]. The results showed that the technology has great potential to cope with the demanding requirements of resonantly exciting atomic transitions of different elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of using the diamond bulk as a Raman laser material, its unique optical properties enabled the development of lasers operating over a wide spectrum due to its giant Raman frequency shift (1332 cm -1 ), large Raman gain (>40 cm/GW @ 532 nm) and ultra-wide transparency window (from DUV all the way to the THz, except for a lossy window from 2.6 -6 µm due to multiphonon-induced absorption [10][11][12][13][14][15]). Furthermore, the excellent thermal properties afforded by diamond (unsurpassed thermal conductivity of 1800 W/m/K at 300 K and low thermo-optic coefficient of the order of 10 -5 K -1 ) along with negligible birefringence [16] make it an ideal material for high-power Raman lasing with greatly reduced thermal lensing effects at the kW average power level [17].…”
Section: Measurement Principlementioning
confidence: 99%
“…Carefully engineering the resonators to have high Q factors over a broad wavelength range is necessary if the Raman lasers were to have a wide tuning range at every resonant wavelength 24 . Widely tunable Raman lasers have been well demonstrated in diamond 25 28 , silica 29 , chalcogenide glass 30 , 31 , and aluminum nitride 32 devices. A wide tuning bandwidth of about 100 nm was realized in a single-mode racetrack microresonator fabricated on a diamond waveguide platform with a lasing threshold power of 85 mW 33 .…”
Section: Introductionmentioning
confidence: 99%